Konsep Pluralis-Multikultural dan Implementasi dalam Dunia Pendidikan Said Subhan Posangi - Said Subhan Posangi (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2018)
Abstract: Indonesia consists of various racial, ethnic or religious group. Therefore, need awareness of the Society to perform in a more understanding and assessment in education. Discourse on diversity must be addressed wisely so as not to bring any conflict, as had happened some time ago. Pluralist-multicultural concept seems appropriate to be applied in education as an understanding and assessment of diversity in Indonesia to raise harmony together and prevent the conflict. Education made special shots because this is where the search process beginning stock of one’s life meaning. In education will form a value system that direct a person to move and act based on the value system that he belong to. Keyword: Concept, Pluralist, Multicultural, and Education.